On War and Leadership : The Words of Combat Commanders from Frederick the Great to Norman Schwarzkopf - Connelly, Owen, 1924-2011 (Princeton: New Jersey Princeton University Press, 2002)
Takes us behind the scenes and to the front lines of the major wars through the words of twenty combat commanders. This book offers a take on military history by those who lived it. The leaders showcased here range from Frederick the Great to Norman Schwarzkopf. They include such diverse figures as Napoleon Bonaparte.
Includes Notes, Bibliography and Index.
Keywords: Military History -- Command of Troops -- Leadership